Multi-scale damage modelling of 3D woven composites under uni-axial tension. (10th May 2016) - Dai, S.; Cunningham, P.R.
Abstract: This paper presents a detailed numerical analysis of two types of 3D woven composite architecture. a unit cell, full finite element meso model, and a mosaic macro model are developed to simulate the elastic and damage progression behaviour of the two weave types. Both models predicted the tensile modulus and strength within 20% of the experimentally measured values, and the predicted failure sequence was similar to the experimental observation.